2021
DOI: 10.1101/2021.02.23.432454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of variation between groups through time in fish shoal collective motion

Abstract: Despite extensive interest in the dynamic interactions between individuals that drive collective motion in animal groups, the dynamics of collective motion over longer time frames are understudied. Using three-spined sticklebacks, Gasterosteus aculateus, randomly assigned to twelve shoals of eight fish, we tested how six key traits of collective motion changed over shorter (within trials) and longer (between days) timescales under controlled laboratory conditions. Over both timescales, groups became less socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…3 (a). We studied the fish at a variety of ages from 40 dpf (days post fertilisation) to 120 dpf, to capture the effects of fish development [61] and repeated exposure to the experimental environment [62]. This way, we can probe the swimming behaviour at different developmental times of zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…3 (a). We studied the fish at a variety of ages from 40 dpf (days post fertilisation) to 120 dpf, to capture the effects of fish development [61] and repeated exposure to the experimental environment [62]. This way, we can probe the swimming behaviour at different developmental times of zebrafish.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, network metrics from pre-breeding seasons were on average equally repeatable to post-breeding networks. Recent studies on schools of fish also found a rapid divergence of group-level properties over just a few days under laboratory conditions [ 48 ]. Thus, our study adds to a growing body of evidence that differences are emergent to the groups, including groups from relatively anonymous societies (like schooling fish) and those that have strong and consistent social bonds (such as socially monogamous zebra finches).…”
Section: Discussionmentioning
confidence: 99%